Die Nachbarsprache Polnisch aus einer sprachpolitischen und soziolinguistischen Perspektive im Kontext der Mehrsprachigkeit in Europa - Kowlonek-Janczarek, Monika (Glottodidactica, 2009)
The main goal of this article is to discuss the position of Polish language in the European Union, especially in the German-Polish border region. The role of language policy in the process of multilingualism will also be presented.